Characterization of dementia with Lewy bodies (DLB) and mild cognitive impairment using the Lewy body dementia module (LBD‐MOD). Issue 10 (1st April 2021) - Galvin, James E.; Chrisphonte, Stephanie; Cohen, Iris; Greenfield, Keri K.; Kleiman, Michael J.; Moore, Claudia; Riccio, Mary Lou; Rosenfeld, Amie; Shkolnik, Niurka; Walker, Marcia; Chang, Lun‐Ching; Tolea, Magdalena I.
Abstract: Introduction: The National Institute on Aging Alzheimer's Disease Research Center program added the Lewy body dementia module (LBD‐MOD) to the Uniform Data Set to facilitate LBD characterization and distinguish dementia with Lewy bodies (DLB) from Alzheimer's disease (AD). We tested the performance of the LBD‐MOD. Methods: The LBD‐MOD was completed in a single‐site study in 342 participants: 53 controls, 78 AD, and 110 DLB; 79 mild cognitive impairment due to AD (MCI‐AD); and 22 MCI‐DLB. Results: DLB differed from AD in extrapyramidal symptoms, hallucinations, apathy, autonomic features, REM sleep behaviors, daytime sleepiness, cognitive fluctuations, timed attention tasks, and visual perception. MCI‐DLB differed from MCI‐AD in extrapyramidal features, mood, autonomic features, fluctuations, timed attention tasks, and visual perception. Descriptive data on LBD‐MOD measures are provided for reference. Discussion: The LBD‐MOD provided excellent characterization of core and supportive features to differentiate DLB from AD and healthy controls while also characterizing features of MCI‐DLB.